Temporal Imaginations: Mnemonic Frames Against Extractivism in Guatemala - Vaclav Masek Sánchez (International Journal for Crime, Justice and Social Democracy)
What is the role of collective memory in motivating social movements in post-peace Guatemala? Focusing on Indigenous resistance against extractivism, an 18-month (2021-2023) participant-observation project on grassroots campaigns with Defensoria Q’eqch’ and AEPDI documented the Maya-Q’eqchi’ front against the Fenix nickel mining project. Fifteen in-depth interviews with men and women in sites of struggle across El Estor, Izabal and 30 recorded testimonies of survivors of the Guatemalan genocide reveal activists draw on resistance narratives to counter the legacies of settler colonialism. Indigenous activists are mobilizing unified fronts against the state and capital in post-conflict societies, and the mechanism of collective memory plays a crucial role in encouraging political action through the deployment of “temporal imaginations,” which are self-reflecting and retrospective frames that position social movements in history and time. Temporal imaginations provide a way to articulate past injustices and present grievances, cement loyalties, establish goals, and evaluate new challenges.